Intestinal Microbiota: Early Formation, Health Effects, and Correction Ways - Andrey S. Yakushin; Sergey E. Ukraintsev; Mikhail Yu. Denisov ("Paediatrician" Publishers LLC, 2018)
An increase in the prevalence of diseases resulting from disorders of metabolism and immune system functions is largely due to disturbances in the intestinal microbiota composition at an early age. The review  considers the stages and conditions of the natural development of the  intestinal microbiota, starting from the intrauterine period. We  conducted the analysis of possible risk factors for the intestinal  microbiota composition disorders in the pre- and postnatal periods. The  results of modern studies on the association between the intestinal  microbiota composition in infancy and the development of «civilization  diseases» at older ages are given. A separate section is devoted to a  discussion of the efficacy and appropriateness of taking probiotic drugs for disease prevention.